Analysis of the teaching career in primary education in Mexico: Between credentialism and meritocracy - Yazmín Cuevas; Karla Rangel Montalvo (Arizona State University, 2019)
The purpose of this article is to answer the following questions: In Mexico, what has been the development of the teaching career in primary education between 1930 and 2017? What are the changes that have impacted this career in relation to the historical-political context? And what have been the elements and criteria that have oriented such regulation of the teaching profession? In an analysis of laws, regulations and norms, the authors found that Mexico has focused on three career approaches. The first is the credentialist, as a consequence of the development of the nascent education system and the political pacts between the teacher's unions and the State. The second is the transitory approach, which incorporated elements of meritocracy into a credentialist legal structure. The third is the meritocratic, which stands out for the use of performance evaluations for teacher regulation, for which new regulatory instances were created in order to displace the union from regulatory processes. The authors also observed that the particularities of the educational system, as well as the historical-political context, mark specific paths of Mexican teaching regulation.